SWOT Analysis of Artificial Intelligence Implementation in Digital Business Models in Indonesia - Suhara, Ade; Supriandi, Supriandi; Priyana, Yana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the implementation of Artificial Intelligence (AI) in digital business models in Indonesia through a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analytical framework. Using a qualitative research approach, data were obtained from five key informants representing digital business practitioners, technology consultants, policymakers, and academics. The findings indicate that AI enhances operational efficiency, supports personalized customer experiences, and facilitates data-driven decision-making, which collectively strengthen innovation, agility, and competitiveness. Despite these advantages, the study identifies several persistent barriers, including high implementation costs, limited AI-skilled human resources, and challenges related to data quality and cybersecurity. Opportunities are supported by government-led digital transformation programs, such as Making Indonesia 4.0 and the National AI Strategy 2045, the rapid expansion of the digital economy, and continuous advancements in cloud computing and big data analytics. Nevertheless, significant threats remain, such as regulatory uncertainty, ethical concerns over data governance and algorithmic bias, and dependence on foreign technology providers. The study concludes that successful AI integration in Indonesia’s digital business ecosystem requires a strategic balance between technological investment, workforce capability development, and adaptive regulatory frameworks. By strengthening cross-sector collaboration and ensuring ethical, inclusive governance, AI can serve as a key driver of sustainable innovation and long-term competitiveness in Indonesia’s digital economy.